PICMET '07 - 2007 Portland International Conference on Management of Engineering &Amp; Technology 2007
DOI: 10.1109/picmet.2007.4349584
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Six Sigma with Lean Production Practices for Identifying Common Causes of Software Process Variability

Abstract: Six Sigma emphasizes the variability causes search. The special causes are more evident, which favors their identification, while the common causes are more difficult to be identified and solved and, for that, they request a specialists' participation. Many software development process variability causes are common and it is not always possible to have Six Sigma specialists to identify them. An alternative might be the visibility criteria proposed by Lean Production. Instead of this criterion, software enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
2
Order By: Relevance
“…For increasing the quality and the performance, a novel data collection was used to achieve continuous improvement in the service industry. Tonini et al [35] introduced the Lean with Six Sigma process for achieving the error-free products. This approach helped to identify the project mistakes easily so that the projects could be finished more quickly and effective results could be got.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For increasing the quality and the performance, a novel data collection was used to achieve continuous improvement in the service industry. Tonini et al [35] introduced the Lean with Six Sigma process for achieving the error-free products. This approach helped to identify the project mistakes easily so that the projects could be finished more quickly and effective results could be got.…”
Section: Related Workmentioning
confidence: 99%
“…Xu et al [28], Mcllroy and Silverstein, and Sharma [29] showed that Lean Six Sigma could be implemented in the non-manufacturing and service industries and showed a significant improvement. Likewise, implementation of Lean Six Sigma was initiated in software development process by Tonini et al [35]. Later, a software development approach was created using Lean Six Sigma to hold the continuity and change requirements by Pillai et al [37,38].…”
Section: Related Workmentioning
confidence: 99%
“…De acordo com Tonini et al [25], a adoção de práticas do Lean contribuem na identificação das causas de defeitos ou falhas dos produtos e no aumento da participação do time de desenvolvimento de software nos projetos de melhoria (Six Sigma), independentemente dos integrantes desse time serem ou não especialistas em estatística.…”
Section: Trabalhos Relacionadosunclassified
“…Por outro lado, ao estimular a eliminação de todo e qualquer desperdício, o sistema obriga os profissionais a investigarem as causas dos principais problemas, independentemente de serem especiais ou comuns. Ligado a esse ponto, o incentivo, a velocidade e a autonomia das pessoas no trabalho se destacam em qualquer nível hierárquico, para propor rapidamente uma solução eficaz orientada para a resolução do problema (TONINI et al, 2007).…”
Section: Entende Condições Atuais Descoberta Do Conhecimentounclassified